The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1159/000243397
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Caffeine and Zinc on Brain in Newborn Rats

Abstract: The purpose of this study was to determine whether adding zinc to the caffeine-supplemented diet of dams during gestation and lactation would affect brain development in newborn rats. On day 9 of gestation, dams of group 1 were fed a 20% protein diet as a control. Dams of group 2 were fed a 20% protein diet supplemented with caffeine. Dams of group 3 were fed a 20% protein diet supplemented with caffeine and zinc. The amount of caffeine added to the maternal diet was 2 mg/100 g of body weight. The amount of zi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1992
1992
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Another proposed mechanism of action of green coffee on fetal development is that caffeine decreases the zinc content and absorption in the developing fetal brain (Nakamoto and Joseph, 1991;Yazdani et al, 2002). The authors stated that maternal administration of caffeine altered the zinc content in the fetal brain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another proposed mechanism of action of green coffee on fetal development is that caffeine decreases the zinc content and absorption in the developing fetal brain (Nakamoto and Joseph, 1991;Yazdani et al, 2002). The authors stated that maternal administration of caffeine altered the zinc content in the fetal brain.…”
Section: Discussionmentioning
confidence: 99%
“…Kasala et al (2020) related the caffeine-induced neuronal apoptosis in rat pups to disruption in the expression of mitochondrial-associated genes. In addition, the ultrastructural investigation revealed that the highest dose of green coffee induced demyelination and degeneration of the axons in the fetal spinal cord.Interestingly, it has been shown that high doses of caffeine transiently reduce myelin synthesis in postnatal pups(Nakamoto and Joseph, 1991).Additionally,Huang et al (2012) observed that maternal administration of caffeine-induced different ultrastructural changes in the trophoblast cells in a dose-dependent manner. These changes included edematous endoplasmic reticulum, swollen cisternae of rER, degranulation of ribosomes, and heterochromatin clumping.…”
mentioning
confidence: 99%
“…However, as high as 1 g of dietary zinc has been reported to be supplemented in animal studies [24]. A previous study [12] has indi cated that the present amount of zinc supple mentation does not exert toxic effects on dams.…”
Section: Methodsmentioning
confidence: 98%
“…Intravenous caffeine given to the pregnant human female results in fetal tissue levels equivalent to maternal plasma levels [5], In animal studies, caffeine affects brain protein synthesis in the young growing rats [6], min eral content [7] and myelin formation in post natal pups [8]. Caffeine administered to preg nant rat dams in a dose equivalent to ten cups of coffee per day for the second half of preg nancy has shown a decrease in fetal brain weight, cholesterol content, alkaline phospha tase activity and zinc concentration [9], Be cause zinc plays an important role in growth and development [ 10] and is shown to affect the brain in rats [11], the significant decrease in the zinc content in the brain as a result of caffeine intake during the growth period [ 12] could affect the developing brain. The objec tive of the present study was to determine whether zinc supplementation to the mater nal diet modifies the effects of caffeine expo sure during gestation.…”
Section: Introductionmentioning
confidence: 99%